APLIKASI PREBIOTIK UNTUK MENINGKATKAN NILAI KECERNAAN PAKAN IKAN NILA (Oreochromis niloticus) - Afzriansyah Afzriansyah; Saifullah Saifullah; Achmad Noerkhaerin Putra (JURNAL PERIKANAN DAN KELAUTAN, 2014)
Tilapia (Oreochromis niloticus) is one freshwater fish which have high economic value. In the culture of tilapia, feed is the most important external factors. The optimal levels of protein to support the growth of tilapia ranged from 28-40 %, however the digested one is only about 20-25 % and the others were wasted and accumulated in the water. An attempt have been done to improve the feed digestibility value in tilapia by using the prebiotics addition to the feed. The aims of this research was to evaluate the addition of prebiotics to the feed to improve feed digestibility value in tilapia. The parameters measured were the amount of feed intake, the total population of bacteria, protein digestibility, fat digestibility, total digestibility, protein retention, fatty retention, specific growth rate, survival rate and feed efficiency. The results showed that the protein digestibility was 92.25%, fatty digestibility was 96.61% and total digestibility was 86.77%. The best results of feed was found in the addition of 1% prebiotic.Keyword: digestibility, prebiotics, tilapia